Collectibility Insights: Financial Analysis - Faridatul Ulla; Anita Handayani (INNOVATION RESEARCH JOURNAL, 2023)
The General Regional Company BPR Bank Gresik is one of the banks owned by the Gresik Regency government which provides credit facilities. Disbursing credit does not always run smoothly, because in disbursing credit there is definitely a risk. One of the risks in distributing credit is the existence of problem loans. The size of non-performing loans can be seen from the high level of collection. This research aims to find out, analyze and explain the factors causing and handling credit based on collection in the BPR Bank Gresik Perumda. The research method used is descriptive with a qualitative approach. Data analysis was carried out using the Miles and Huberman model, which involves data collection, data reduction, data presentation, and drawing conclusions. The research results show that the factors causing the increase in collection come from internal and external banks. Handling is carried out differently depending on the level of collection which involves various steps, including telephone warnings, direct billing to the house, warning letters, summons letters, restructuring, placing banners on collateral, cessie, small claims court, and taking over the debtor's collateral.